THE LEVEL OF ORAL COMMUNICATION APPREHENSION AMONG ENGLISH DEPARTMENT STUDENTS IN PRESENTATION CLASS AT RIAU ISLAMIC UNIVERSITY - Vitri Angraini Hardi (Universitas Pahlawan Tuanku Tambusai, 2018)
The successful English learners are determined by their ability to communicate in English in daily activities, especially in the teaching and learning process However, it is not a simple task. Some English learners are still struggle to use English to communicate since English is used as Foreign Language in Indonesia. It is experienced even the students have learned English for long years. The university students, English Department students also need struggle to communicate in English. One of the handicaps in acquiring the ability to communicate in a foreign language is called communication apprehension. The individuals fear in facing the communication either real or anticipated causes the students to avoid the communication activity. Then, it resulted the less progress of the students in using the language. Oral communication apprehension is experienced by everyone, especially foreign language learners. It seems as a potential inhibitor for the students to develop their competence and skills in communication. In fact, the existence of communication apprehension are not realized. Unfortunately, the foreign language learners are not consider on it.